First record of the genus Immanus Hulcr & Cognato (Coleoptera: Curculionidae: Scolytinae: Xyleborini) from China, with description of a new species - Lin, Wei; Li, You; Meng, Ling-Zeng (Zootaxa, 2023)
Immanus Hulcr & Cognato, 2013 is reported from China for the first time, with the description and illustration of a new species, Immanus songi sp. nov., based on an adult female collected with a flight intercept trap from Yunnan province, China. A key to all known species of Immanus is given.